Singular therapeutic project as a family approach tool during home visits (Research, Society and Development, 2023)
The Singular Therapeutic Project (PTS), the main working tool of the Family Health Strategy (ESF) in Primary Health Care, enables comprehensive care. The objective was to describe the steps that constituted the construction of a PTS together with the patient and his support network in the practice scenario in a community in Duque de Caxias, RJ, portraying the importance of this tool of family approach during the Home Visit. This is an experience report of medical students at Unigranrio Afya University. The construction of the PTS favored the joint elaboration of the therapeutic plan and, consequently, the strengthening of the bond, since the project was carried out by the academics, their teachers, the Community Health Agent (CHA) of the local Basic Health Unit (UBS), the patient and their support network. Thus, the experience enabled a theoretical-practical enrichment for personal and professional training, in addition to an expanded view of family dynamics and the illness process, thus favoring care management.